2022
DOI: 10.3389/fpsyg.2022.969657
|View full text |Cite
|
Sign up to set email alerts
|

The impact of self-compassionate mindfulness on online learning behavioral engagement of international students during COVID-19: Positive emotion and self-improvement motivation as mediators

Abstract: Focusing on the domain of self-compassion, this study explored the promotion mechanism of online learning behavioral engagement (OLBE) of international students in China under COVID-19. Positive emotion and self-improvement motivation were selected as mediators. Participants were 606 international students from 8 countries who were studying online in their own countries due to the international travel restriction of COVID-19. Results showed positive emotion and self-improvement motivation completely mediated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Some studies had shown that reducing negative emotions can improve learning motivation (Huang et al, 2016), academic stress can predict motivation (Karaman & Watson, 2017). At the same time, a study on Chinese foreign students (Chen et al, 2022) showed that students with higher self-compassionate mindfulness levels and positive emotions have higher motivation for self-improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies had shown that reducing negative emotions can improve learning motivation (Huang et al, 2016), academic stress can predict motivation (Karaman & Watson, 2017). At the same time, a study on Chinese foreign students (Chen et al, 2022) showed that students with higher self-compassionate mindfulness levels and positive emotions have higher motivation for self-improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies had shown that reducing negative emotions can improve learning motivation (43), academic stress can predict motivation (20). At the same time, a study on Chinese foreign students (44) showed that students with higher self-compassionate mindfulness levels and positive emotions have higher motivation for self-improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Under the background of COVID-19 pandemic, the learning modes of students were to be altered as they were forced to study online. And changes have taken place, for example, students have less time and depth of interaction with classmates and teachers, less peer comparison pressure and supervision of teachers, and less extrinsic motivation [37]. It is estimated that studies these years have been focusing more on how to provide efficiency assurance for online learning education, and foreign language enjoyment has been of great concerns in studies of emotions.…”
Section: Discussionmentioning
confidence: 99%